ANALISIS IMPLEMENTASI KEBIJAKAN RELAKSASI PAJAK DALAM RANGKA PEMULIHAN EKONOMI PADA SEKTOR PARIWISATA YANG TERDAMPAK COVID-19 - Kaca Dian Meila (Syntax Corporation, 2022)
This study aims to determine the magnitude of the impact covid-19 in the tax prayers tourism sector, the benefits of tax relaxation in the tourism sector, and the implementation of the tax relaxation policy in the context of economic recovery in the tourism sector affected by covid-19. This research is a type of qualitative research method using interviews which are processed using coding techniques and distributing questionnaires to tax payers. The sample obtained by purposive sampling method as many as 60 respondents. The result show that the percentage of tax payers who take advantage of tax relaxtation is 53,33% for tax payers who have business in the hotel sector, 42,11% for tax payers who have a business in the restaurant sector and 27,27% for tax payers who have a business in the enterataiment business. This shows that there are still tax payers who have not been able to take advantage of tax relaxation